Laminate and virtual reality display device

By applying a second composition containing different liquid crystal compounds to the first cholesteric liquid crystal layer of the laminated body, the second cholesteric liquid crystal layer is formed, and the problem of insufficient reflectivity of the existing laminated body is solved, thereby achieving a high reflectivity and simplification of the manufacturing process.

CN119856083APending Publication Date: 2025-04-18FUJIFILM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380064588.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-09-15
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing laminated body with two or more cholesteric liquid crystal layers has not met the requirements in terms of reflectivity, and the manufacturing process is complicated, so it needs to be simplified to improve the reflectivity.

Method used

By applying a second composition containing different liquid crystal compounds on the first cholesteric liquid crystal layer, the second cholesteric liquid crystal layer is formed, and the orientation and thickness of the liquid crystal layer are controlled by a specific structure and treatment method to improve the reflectivity.

Benefits of technology

The high reflectivity of the stacked body is realized, suitable for virtual reality display devices, and the manufacturing process is simplified and the process complexity is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005301733450000231
    Figure BDA0005301733450000231
  • Figure BDA0005301733450000251
    Figure BDA0005301733450000251
  • Figure BDA0005301733450000261
    Figure BDA0005301733450000261
Patent Text Reader

Abstract

The present invention addresses the problem of providing a laminate comprising two cholesteric liquid crystal layers, wherein the cholesteric liquid crystal layers formed by a coating process have high reflectivity. A laminate according to the present invention comprises: a first cholesteric liquid crystal layer formed using a first composition containing a first liquid crystal compound; and a second cholesteric liquid crystal layer formed on the first cholesteric liquid crystal layer by a coating process using a second composition containing a second liquid crystal compound, the first liquid crystal compound being a discotic liquid crystal compound, and the first liquid crystal compound and the second liquid crystal compound being different compounds. Among the open and dark lines derived from the cholesteric liquid crystal phase, the dark line farthest from the first cholesteric liquid crystal layer is defined as a surface layer dark line, and the dark line closest to the intermediate position in the thickness direction of the second cholesteric liquid crystal layer is defined as an intermediate dark line. The ratio of the width of the area where the surface layer dark lines exist to the width of the middle dark lines is 1.2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a stacked body and a virtual reality display device comprising the stacked body. Background Art

[0002] Laminated bodies having two or more layers formed using a composition containing a liquid crystal compound are used for various applications. Such laminated bodies are generally used for optical applications due to the optical properties derived from the liquid crystal compound contained in the laminated body.

[0003] For example, Patent Document 1 discloses an optical film (laminate) comprising a first optically anisotropic layer and a second optically anisotropic layer disposed on the surface of the first optically anisotropic layer, wherein the first optically anisotropic layer is a layer in which a liquid crystal compound is oriented and polymerized to be fixed, and the surface inclination angle of the liquid crystal compound on the side in contact with the second optically anisotropic layer is 5 to 80°.

[0004] On the other hand, in the above-mentioned laminated body, there is also known a method of using a layer (cholesteric liquid crystal layer) in which the alignment direction of a cholesteric liquid crystal compound is fixed.

[0005] Previous technical literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2014-142618 Summary of the invention

[0008] Technical issues to be solved by the invention

[0009] A laminate having two or more cholesteric liquid crystal layers may be used as a device utilizing the characteristics of the cholesteric liquid crystal layers.

[0010] In this case, the reflectivity of electromagnetic waves in a specific wavelength region (hereinafter, also simply referred to as “reflectivity”) is required to be high.

[0011] Furthermore, from the viewpoint of being able to reduce the manufacturing process, the manufacture of the laminate having two or more cholesteric liquid crystal layers as described above is preferably carried out by sequentially applying a composition containing a liquid crystal compound. That is, it is preferred that one cholesteric liquid crystal layer is formed by a composition containing a liquid crystal compound, and another cholesteric liquid crystal layer is formed by applying a composition containing a liquid crystal compound to the formed cholesteric liquid crystal layer.

[0012] The present inventors referred to the method described in Patent Document 1 and sequentially coated a composition containing a liquid crystal compound to produce a laminate having two cholesteric liquid crystal layers. They found that the reflectivity of the obtained laminate did not reach the currently required level and needed to be improved.

[0013] Therefore, an object of the present invention is to provide a laminated body including two cholesteric liquid crystal layers, wherein the cholesteric liquid crystal layers formed by coating treatment have high reflectance.

[0014] Furthermore, another object of the present invention is to provide a virtual reality display device using a laminate.

[0015] Means for solving technical problems

[0016] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention. Specifically, they have found that the above-mentioned problems can be solved by the following configuration.

[0017] [1] A laminate comprising:

[0018] a first cholesteric liquid crystal layer formed using a first composition including a first liquid crystal compound; and

[0019] a second cholesteric liquid crystal layer formed on the first cholesteric liquid crystal layer by coating with a second composition containing a second liquid crystal compound;

[0020] The first liquid crystal compound is a discotic liquid crystal compound.

[0021] The first liquid crystal compound and the second liquid crystal compound are different compounds, and

[0022] When, among the bright lines and dark lines derived from the cholesteric liquid crystal phase of the second cholesteric liquid crystal layer observed by cross-section observation using a scanning electron microscope, the dark line at the position farthest from the first cholesteric liquid crystal layer side is defined as a surface dark line, and the dark line at the position closest to the middle position in the thickness direction of the second cholesteric liquid crystal layer is defined as a middle dark line,

[0023] A ratio of a width of a region where the surface dark line exists in a thickness direction of the second cholesteric liquid crystal layer to a width of the intermediate dark line in the thickness direction of the second cholesteric liquid crystal layer is 1.2 or less.

[0024] [2] The laminate according to [1], wherein

[0025] A ratio of a width of a region where the middle dark line exists in a thickness direction of the second cholesteric liquid crystal layer to a width of the middle dark line in the thickness direction of the second cholesteric liquid crystal layer is 3.0 or less.

[0026] [3] A laminate comprising:

[0027] a first cholesteric liquid crystal layer formed using a first composition including a first liquid crystal compound; and

[0028] a second cholesteric liquid crystal layer formed on the first cholesteric liquid crystal layer by coating with a second composition containing a second liquid crystal compound;

[0029] The first liquid crystal compound is a discotic liquid crystal compound.

[0030] The first liquid crystal compound is different from the second liquid crystal compound,

[0031] The second cholesteric liquid crystal layer includes a surfactant.

[0032] On the surface of the second cholesteric liquid crystal layer on the side opposite to the first cholesteric liquid crystal layer, the number of aggregates of the surfactant having a major diameter of 0.5 μm or more is less than 10,000 / mm 2 .

[0033] [4] The laminate according to [3], wherein:

[0034] The surfactant includes a first surfactant and a second surfactant.

[0035] [5] The laminate according to [4], wherein:

[0036] The first surfactant is a surfactant contained in the first composition.

[0037] The first surfactant is liquid crystal, and the phase transition temperature from the liquid crystal phase to the isotropic liquid phase is 100° C. or higher, or

[0038] The first surfactant is non-liquid crystal and has a melting point of 90° C. or higher.

[0039] [6] The laminate according to [4] or [5], wherein

[0040] The first surfactant has an aromatic ring structure having four or more rings.

[0041] [7] The laminate according to any one of [4] to [6], wherein

[0042] The molecular weight of the first surfactant is 5,000 or less.

[0043] [8] The laminate according to any one of [4] to [7], wherein

[0044] The first surfactant is represented by formula (11) described below.

[0045] [9] The laminate according to any one of [3] to [8], wherein

[0046] The second liquid crystal compound is a rod-like liquid crystal compound.

[0047]

[10] A virtual reality display device comprising the stacked body described in any one of [1] to [9].

[0048] Effects of the Invention

[0049] According to the present invention, it is possible to provide a laminated body including two cholesteric liquid crystal layers, wherein the cholesteric liquid crystal layers formed by coating treatment have high reflectance.

[0050] Furthermore, according to the present invention, a virtual reality display device using a laminate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 This is a diagram showing an example of the laminate of the present invention.

[0052] Figure 2 yes Figure 1 Schematic diagram of an enlarged cross-sectional view of the vicinity of the side opposite to the first cholesteric liquid crystal layer A10 side of the second cholesteric liquid crystal layer A12 in the stacked structure shown, taken with a scanning electron microscope. DETAILED DESCRIPTION

[0053] Hereinafter, the present invention will be described in detail.

[0054] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.

[0055] The meaning of each description in this specification is shown below.

[0056] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0057] In this specification, when the first liquid crystal compound and the second liquid crystal compound are different compounds, it includes a mode in which the first liquid crystal compound is a disc-shaped liquid crystal compound and the second liquid crystal compound is a rod-shaped liquid crystal compound and a mode in which the first liquid crystal compound is a disc-shaped liquid crystal compound and the second liquid crystal compound is a disc-shaped liquid crystal compound different from the first liquid crystal compound.

[0058] [First Embodiment of Laminated Body]

[0059] A first embodiment of the laminate of the present invention is a laminate including a first cholesteric liquid crystal layer A, which is formed using a first composition A containing a first liquid crystal compound A, and a second cholesteric liquid crystal layer A, which is formed on the first cholesteric liquid crystal layer A by coating using a second composition A containing a second liquid crystal compound A. Here, the first liquid crystal compound A contained in the first composition A is a discotic liquid crystal compound, and the first liquid crystal compound A contained in the first composition A and the second liquid crystal compound A contained in the second composition A are different compounds.

[0060] Furthermore, when, among the bright lines and dark lines originating from the cholesteric liquid crystal phase of the second cholesteric liquid crystal layer A observed by cross-section observation using a scanning electron microscope, the dark line farthest from the first cholesteric liquid crystal layer A is set as a surface dark line, and the dark line closest to the middle position in the thickness direction of the second cholesteric liquid crystal layer A is set as an intermediate dark line, the ratio of the width of the region where the surface dark line exists in the thickness direction of the second cholesteric liquid crystal layer A to the width of the intermediate dark line in the thickness direction of the second cholesteric liquid crystal layer A is less than 1.2.

[0061] The cholesteric liquid crystal layer refers to a layer in which a cholesterically aligned liquid crystal compound is fixed.

[0062] A first embodiment of the laminate will be described with reference to the drawings.

[0063] like Figure 1 As shown, the stacked body 100 is composed of a first cholesteric liquid crystal layer A10 and a second cholesteric liquid crystal layer A12. The first cholesteric liquid crystal layer A10 is formed using a first composition A containing a first liquid crystal compound A. In addition, the second cholesteric liquid crystal layer A12 is formed on the first cholesteric liquid crystal layer A10 using a second composition A containing a second liquid crystal compound A by coating.

[0064] Generally, when a cross-section of a cholesteric liquid crystal layer is observed using a scanning electron microscope, a stripe pattern is observed in which bright lines and dark lines originating from the cholesteric liquid crystal phase are alternately stacked in the thickness direction. Figure 1 The above-described stripe pattern was also observed in cross-sectional observation using a scanning electron microscope in the first cholesteric liquid crystal layer A10 and the second cholesteric liquid crystal layer A12.

[0065] exist Figure 2, a schematic diagram of an enlarged cross-sectional view of the second cholesteric liquid crystal layer A12 near the side opposite to the first cholesteric liquid crystal layer A10 side using a scanning electron microscope is shown. Figure 2 , the width of the middle dark line and the width of the area where the surface dark line exists are explained.

[0066] In the second cholesteric liquid crystal layer A12, bright lines 26 and dark lines 28 derived from the cholesteric liquid crystal phase are observed to alternately exist in the thickness direction of the second cholesteric liquid crystal layer A12. Figure 2 In FIG. 1 , the middle position in the thickness direction of the second cholesteric liquid crystal layer A12 is represented as a middle position M.

[0067] Here, the dark line 28 at the position closest to the middle position M is referred to as the middle dark line 28b, and the dark line 28 at the position farthest from the first cholesteric liquid crystal layer 10A is referred to as the surface dark line 28a. Figure 2 In FIG. 2 , the surface dark lines 28 a are arranged in a wave shape having an amplitude in the thickness direction of the second cholesteric liquid crystal layer A12 .

[0068] The second cholesteric liquid crystal layer A12 is a layer formed by coating. Generally, when a cholesteric liquid crystal layer is formed by coating, it is often impossible to fully control the orientation of the liquid crystal compound on the air interface side. Therefore, the bright lines and dark lines on the air interface side originating from the cholesteric liquid crystal phase are prone to become wavy shapes. In contrast, when a cholesteric liquid crystal layer is formed by coating, the liquid crystal compound is easily oriented at the middle position in the thickness direction of the cholesteric liquid crystal layer, and as a result, straight bright lines and dark lines are easily formed.

[0069] like Figure 2 As shown, the width Wb corresponds to the width of the above-mentioned middle dark line 28b.

[0070] And, if Figure 2 As shown, the region width Wra corresponds to the width of the region where the surface dark line 28a exists in the thickness direction of the second cholesteric liquid crystal layer A12. The region width Wra also corresponds to the length of the surface dark line 28a projected in the thickness direction in the cross-sectional observation diagram under a scanning electron microscope.

[0071] In the present embodiment, the ratio of the region width Wra to the width Wb (Wra / Wb) is 1.2 or less, preferably 1.1 or less, and more preferably 1.05 or less. The lower limit is not particularly limited, but 1.0 is an example.

[0072] In addition, a value of the ratio (Wra / Wb) close to 1.0 indicates that the surface dark line does not extend (for example, in a wavy state) in the thickness direction of the second cholesteric liquid crystal layer A, but indicates that the surface dark line exists linearly. It is believed that the above state reflects that the orientation of the second liquid crystal compound A in the second cholesteric liquid crystal layer A is not disordered. Although the mechanism is not clear, if the above state is reached, it is believed that the reflection in an undesirable direction based on the second liquid crystal compound A is suppressed, and the reflectivity of the cholesteric liquid crystal layer becomes higher.

[0073] A specific method for obtaining the region width Wra and the width Wb will be described below.

[0074] Cross-sectional observation when determining the region width Wra and the region width Wb is performed by the following procedure.

[0075] First, an epoxy resin is used to embed a laminate including a first cholesteric liquid crystal layer A and a second cholesteric liquid crystal layer A. The embedded laminate is cut with an ultra-thin slicer to obtain an observation sample showing a cross section of the laminate. When obtaining the observation sample, cutting is performed in a direction perpendicular to the surface of the laminate. Cutting by an ultra-thin slicer is performed in a manner such that the thickness of the cut slice becomes 200 nm.

[0076] In order to ensure the conductivity of the surface, the surface of the obtained observation sample was subjected to carbon vapor deposition treatment.

[0077] Then, the observation slice is observed by a scanning electron microscope (SEM). As SEM, for example, "S-4800" manufactured by Hitachi High-Tech Corp. can be used. For observation based on SEM, the acceleration voltage is set to 2 kV, and a secondary electron image is obtained at a magnification of 20,000 times. In addition, the acceleration voltage and magnification can be appropriately changed according to the observation object.

[0078] The secondary electron image (observation image) obtained at this time is usually a grayscale image with a bit depth of 8 bits (0 to 255) per pixel. The larger the value represented by each pixel, the closer it is to white, and the smaller the value represented by each pixel, the closer it is to black.

[0079] According to the above-described observation sequence, an image (observation image) in which bright lines and dark lines derived from the cholesteric liquid crystal phase of the second cholesteric liquid crystal layer A can be obtained.

[0080] The observation image obtained in the above-mentioned procedure is analyzed in the following procedure to obtain the region width Wra and the width Wb.

[0081] First, the average brightness which is the average brightness of the brightness of the brightest pixel and the brightness of the darkest pixel in the area corresponding to the second cholesteric liquid crystal layer A of the observation image is obtained and used as a threshold.

[0082] In the observed image, the thickness of the second cholesteric liquid crystal layer A was measured to obtain an average thickness of the second cholesteric liquid crystal layer A. The average thickness was measured at five locations and the arithmetic average thereof was obtained.

[0083] Next, in the observed image, the following image processing is performed to obtain a processed observed image: among each pixel, pixels darker (smaller value) than the above threshold are set to 0 (black), and pixels brighter (larger value) than the above threshold are set to 1 (white). In the processed observed image, the area of ​​the bright line becomes white, and the area of ​​the dark line becomes black.

[0084] In the processed observation image, the dark line closest to the middle position in the thickness direction of the second cholesteric liquid crystal layer A is obtained (at Figure 2 The average width of the middle dark line 28b) is taken as the width Wb. The average width of the dark line is measured at five locations in the thickness direction of the second cholesteric liquid crystal layer A, and the arithmetic average thereof is taken as the average width.

[0085] Furthermore, in the processed observed image, in the thickness direction of the second cholesteric liquid crystal layer A, the dark line at the position farthest from the first cholesteric liquid crystal layer A side (in Figure 2 The width of the region where the surface dark line 28a exists is taken as the region width Wra. The region width is measured from the position where the dark line exists on the side closest to the first cholesteric liquid crystal layer A to the position where the dark line exists on the side farthest from the first cholesteric liquid crystal layer A in the thickness direction of the second cholesteric liquid crystal layer A.

[0086] By the above method, the area width Wra and the area width Wb are obtained.

[0087] In addition, in the processed observation image, a discontinuous black area is sometimes observed near the surface of the second cholesteric liquid crystal layer A on the side opposite to the first cholesteric liquid crystal layer A, but this is not a dark line. The dark line refers to a portion of the black area that exists continuously in a direction perpendicular to the thickness direction of the second cholesteric liquid crystal layer A in the processed observation image.

[0088] In addition, similarly to the step of obtaining the region width Wra, a dark line (at the position closest to the middle position in the thickness direction of the second cholesteric liquid crystal layer A) is also obtained. Figure 2” is the width of the region where the middle dark line 28b exists (hereinafter also referred to as “region width Wrb”).

[0089] Here, the ratio of the region width Wrb to the width Wb (region width Wrb / width Wb) is preferably 3.0 or less, more preferably 1.2 or less, and further preferably 1.1 or less. The lower limit of the ratio of the region width Wrb to the width Wb is 1.0.

[0090] The value of the ratio of the region width Wrb to the width Wb being close to 1.0 indicates that the dark line at the position closest to the middle position in the thickness direction of the second cholesteric B liquid crystal layer A does not extend (for example, in a wavy state) in the thickness direction of the second cholesteric liquid crystal layer A, but that the dark line exists linearly. If the value of the ratio of the region width Wrb to the width Wb is within the preferred range, it is easy to increase the reflectivity of the cholesteric liquid crystal layer.

[0091] Hereinafter, each structure of the first embodiment of the laminate and the materials used in each structure will be described.

[0092] <First cholesteric liquid crystal layer A>

[0093] The first embodiment of the laminated body of the present invention includes a first cholesteric liquid crystal layer A formed using a first composition A containing a first liquid crystal compound A. That is, the first cholesteric liquid crystal layer A is a layer obtained by fixing the cholesterically aligned first liquid crystal compound A. Therefore, the first cholesteric liquid crystal layer A may contain components derived from components contained in the first composition A described later.

[0094] The layer formed by fixing the first liquid crystal compound A in the cholesteric orientation can be any layer as long as the orientation morphology is not changed by an external field or external force. In addition, in the first cholesteric liquid crystal layer A, as long as the optical properties of the cholesteric liquid crystal phase are maintained in the layer, the first liquid crystal compound A in the first cholesteric liquid crystal layer A may no longer show liquid crystal properties. For example, the first liquid crystal compound A may be converted to a high molecular weight by a curing reaction, thereby losing liquid crystal properties.

[0095] The first cholesteric liquid crystal layer A is capable of reflecting electromagnetic waves (light) in a specific wavelength range through the first liquid crystal compound A which is cholesterically oriented. The center wavelength λ of the light reflected by the first cholesteric liquid crystal layer A depends on the pitch P (= period of the spiral) of the spiral structure in the cholesteric liquid crystal phase, and is expressed by the relationship λ=n×P using the average refractive index n of the first cholesteric liquid crystal layer A. In addition, the center wavelength of the light reflected by the first cholesteric liquid crystal layer A can be determined as follows. If the transmission spectrum of the first cholesteric liquid crystal layer A is measured from the normal direction of the liquid crystal layer 1 using a spectrophotometer UV3150 (SHIMADZU CORPORATION), a spectrum having a peak with reduced transmittance can be obtained in the region near the center wavelength λ. Among them, among the two wavelengths with a transmittance of 1 / 2 of the maximum peak value, the value of the wavelength on the short wavelength side is set to λ. l (nm), the value of the wavelength on the long wavelength side is λ h (nm), and the central wavelength λ of the reflected light is calculated by the following formula.

[0096] λ=(λ l +λ h ) / 2

[0097] The central wavelength λ of the light reflected by the first cholesteric liquid crystal layer A is not particularly limited, but is preferably within the visible light region (wavelength 400 to 700 nm).

[0098] The reflectance of the first cholesteric liquid crystal layer A at the central wavelength λ is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more. The upper limit of the reflectance is 50% or less.

[0099] The pitch of the cholesteric liquid crystal phase varies depending on the type of chiral reagent used with the first liquid crystal compound A and its added concentration. By adjusting any one or more of the above, a cholesteric liquid crystal phase with a desired pitch can be obtained. In addition, regarding the method for measuring the rotation direction and pitch of the spiral, the method described in "Introduction to Liquid Crystal Chemistry Experiments" edited by the Liquid Crystal Society of Japan and published by Sigma in 2007, page 46 and "Liquid Crystal Handbook" Liquid Crystal Handbook Editorial Committee Maruzen, page 196 can be used.

[0100] Regarding the formation of the first cholesteric liquid crystal layer A, when the first composition A containing a surfactant is used, in the first cholesteric liquid crystal layer A, a large amount of surfactant is usually contained near the interface with the second cholesteric liquid crystal layer A. As a method for confirming the distribution of the surfactant, for example, a method of analyzing the secondary ion intensity derived from the surfactant in the depth direction by using time-of-flight secondary ion mass spectrometry (TOF-SIMS: Time-of-Flight Secondary Ion Mass Spectrometry) while ion sputtering can be cited. Regarding TOF-SIMS, it is specifically described in "Surface Analysis Technology Series Secondary Ion Mass Spectrometry" compiled by the Japanese Surface Science Society Maruzen Co., Ltd. (published in 1999). In addition, when analyzing the components in the depth direction of the stack by TOF-SIMS while irradiating the ion beam, the following series of operations are repeated: after performing a component analysis of the surface depth region 1 to 2 nm, the next surface depth region 1 to 2 nm is further analyzed by using the ion beam to penetrate hundreds of nm from 1 nm in the depth direction.

[0101] The thickness of the first cholesteric liquid crystal layer A is preferably 0.1 to 10 μm, more preferably 0.3 to 5 μm.

[0102] Hereinafter, the first composition A used for forming the first cholesteric liquid crystal layer A will be described.

[0103] <First Composition A>

[0104] The first composition A used for forming the first cholesteric liquid crystal layer A contains a first liquid crystal compound A.

[0105] Hereinafter, the components contained in the first composition A and the components that may be contained will be described.

[0106] (1st liquid crystal compound A)

[0107] The first liquid crystal compound A is not particularly limited as long as it is a discotic liquid crystal compound, and a known discotic liquid crystal compound can be used. The first liquid crystal compound A is selected to be a compound different from the second liquid crystal compound A described below.

[0108] As a method for causing the first liquid crystal compound A to undergo cholesteric alignment, for example, there is a method of using a first composition A containing the first liquid crystal compound A and a chiral agent.

[0109] The first liquid crystal compound A may be a polymerizable liquid crystal compound having a polymerizable group. The first liquid crystal compound A is preferably a discotic liquid crystal compound.

[0110] As the polymerizable discotic liquid crystal compound, for example, the discotic liquid crystal compounds described in paragraphs 0020 to 0067 of JP-A-2007-108732 or paragraphs 0013 to 0108 of JP-A-2010-244038 can be preferably used.

[0111] The first liquid crystal compound A may be used alone or in combination of two or more.

[0112] The content of the first liquid crystal compound A in the first composition A is not particularly limited, but is preferably 50% by mass or more, more preferably 70% by mass or more, based on the total solid content in the first composition A. The upper limit is not particularly limited, but is usually 90% by mass or less.

[0113] The solid content refers to a component that can form the first cholesteric liquid crystal layer A after removing the solvent, and is considered a solid content even if the component is in a liquid state.

[0114] (First Surfactant A1)

[0115] The first composition A may contain a first surfactant A1. The first surfactant A1 is preferably a component that is easily concentrated on the air interface side of the coating film when the first composition A is applied and can control the alignment of the first liquid crystal compound A.

[0116] In the first embodiment, the first surfactant A1 is not particularly limited, but it is preferable to use the first surfactant B1 used in the second embodiment described later, including preferred aspects. The preferred properties of the first surfactant A1 are also preferably the same as those of the first surfactant B1.

[0117] By using the first surfactant B1 used in the second embodiment described later, it is easy to adjust the dark line region width / dark line width ratio within the above range.

[0118] The content of the first surfactant A1 is preferably 0.01 to 1% by mass, and more preferably 0.05 to 0.5% by mass, based on the total solid content of the first composition A.

[0119] (Solvent)

[0120] The first composition A may contain a solvent.

[0121] The solvent is not particularly limited as long as it can dissolve the components contained in the first composition A. Examples of the solvent include ester solvents, ether solvents, amide solvents, carbonate solvents, ketone solvents, aliphatic hydrocarbon solvents, alicyclic hydrocarbon solvents, aromatic hydrocarbon solvents, halocarbon solvents, water, and alcohol solvents.

[0122] The solvent may be used alone or in combination of two or more.

[0123] (Other ingredients)

[0124] The first composition A may contain other components in addition to the above-mentioned components.

[0125] For example, the first composition A may contain a polymerization initiator. When the first composition A contains a polymerization initiator, polymerization of the polymerizable liquid crystal compound proceeds more efficiently.

[0126] As the polymerization initiator, a known polymerization initiator may be mentioned, and a photopolymerization initiator and a thermal polymerization initiator may be mentioned, and a photopolymerization initiator is preferred.

[0127] The content of the polymerization initiator in the first composition A is not particularly limited, but is preferably 0.01 to 20% by mass, more preferably 0.5 to 10% by mass, based on the total solid content in the first composition A.

[0128] Furthermore, the first composition A may contain a chiral reagent as another component.

[0129] When the first composition A contains a chiral agent, the first liquid crystal compound A can be twisted and aligned along the helical axis.

[0130] The type of chiral agent is not particularly limited, and any of the known chiral agents (e.g., "Handbook of Liquid Crystal Devices" compiled by the 142nd Committee of the Japan Society for the Promotion of Science, Chapter 3, Item 4-3, Chiral Agents for TN and STN, p. 199, 1989) can be used.

[0131] As a chiral agent, a photosensitive chiral agent (hereinafter, also referred to as "chiral agent A") whose helical twisting force changes by light irradiation can be used. Chiral agent A can be liquid crystalline or non-liquid crystalline. Chiral agent A usually contains asymmetric carbon atoms. In addition, chiral agent A can be an axially asymmetric compound or a surface asymmetric compound that does not contain an asymmetric carbon atom.

[0132] The chiral agent A may have a polymerizable group.

[0133] The first composition A may contain two or more chiral agents A, or may contain at least one chiral agent A and at least one chiral agent whose helical twisting force does not change upon light irradiation.

[0134] The content of the chiral agent A in the first composition A is not particularly limited, but from the viewpoint of facilitating uniform orientation of the first liquid crystal compound A, it is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 2.0% by mass or less, relative to the total mass of the first liquid crystal compound A. The lower limit of the content of the chiral agent A is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and further preferably 0.05% by mass or more, relative to the total mass of the first liquid crystal compound A.

[0135] <Second cholesteric liquid crystal layer A>

[0136] The first embodiment of the laminate of the present invention includes a second cholesteric liquid crystal layer A, which is formed on the first cholesteric liquid crystal layer A by coating using a second composition A containing a second liquid crystal compound A. That is, the second cholesteric liquid crystal layer A is a layer obtained by fixing the cholesterically aligned second liquid crystal compound A. Therefore, the second cholesteric liquid crystal layer A may include components derived from the components included in the second composition A described later.

[0137] The layer formed by fixing the cholesterically oriented second liquid crystal compound A can be a layer in which the orientation morphology is not changed by an external field or external force. In addition, in the second cholesteric liquid crystal layer A, as long as the optical properties of the cholesteric liquid crystal phase are maintained in the layer, the second liquid crystal compound A in the second cholesteric liquid crystal layer A may no longer show liquid crystal properties. For example, the second liquid crystal compound A may be converted to a high molecular weight by a curing reaction, thereby losing liquid crystal properties.

[0138] The second cholesteric liquid crystal layer A can reflect electromagnetic waves (light) in a specific wavelength range through the second liquid crystal compound A in a cholesteric orientation. The center wavelength λ of the light reflected by the second cholesteric liquid crystal layer A depends on the pitch P (= period of the spiral) of the spiral structure in the cholesteric liquid crystal phase, and is expressed by the relationship λ=n×P using the average refractive index n of the second cholesteric liquid crystal layer A. In addition, the center wavelength of the light reflected by the second cholesteric liquid crystal layer A can be obtained in the same manner as the center wavelength of the light reflected by the first cholesteric liquid crystal layer A.

[0139] The central wavelength λ of the light reflected by the second cholesteric liquid crystal layer A is not particularly limited, but is preferably within the visible light region.

[0140] The reflectance of the second cholesteric liquid crystal layer A at the central wavelength λ is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more. The upper limit of the reflectance is 50% or less.

[0141] The pitch of the cholesteric liquid crystal phase varies depending on the type of chiral agent used together with the second liquid crystal compound A and its added concentration. By adjusting any one or more of the above, a cholesteric liquid crystal phase having a desired pitch can be obtained.

[0142] The second cholesteric liquid crystal layer A may include the components included in the first composition A used for forming the first cholesteric liquid crystal layer A. For example, the second cholesteric liquid crystal layer A may include the first surfactant.

[0143] In addition, regarding the formation of the second cholesteric liquid crystal layer A, when the second composition A containing a surfactant is used, a large amount of the surfactant is usually contained on the surface of the second cholesteric liquid crystal layer A on the side opposite to the first cholesteric liquid crystal layer A. The distribution of the surfactant in the second cholesteric liquid crystal layer A can be confirmed by the same method as described in the first cholesteric liquid crystal layer A.

[0144] The thickness of the second cholesteric liquid crystal layer A is preferably 0.1 to 10 μm, more preferably 0.3 to 5 μm.

[0145] Hereinafter, the second composition A used for forming the second cholesteric liquid crystal layer A will be described.

[0146] <Second Composition A>

[0147] The second composition A used for forming the second cholesteric liquid crystal layer A contains a second liquid crystal compound A.

[0148] Hereinafter, the components contained in the second composition A and the components that may be contained will be described.

[0149] (Second liquid crystal compound A)

[0150] The second liquid crystal compound A is not particularly limited, and a known liquid crystal compound can be used. Among them, the second liquid crystal compound A is selected from a compound different from the first liquid crystal compound A. As the liquid crystal compound, for example, a rod-shaped liquid crystal compound and a disc-shaped liquid crystal compound can be cited. As a method for making the second liquid crystal compound A cholesteric, for example, a method of using a second composition A containing a second liquid crystal compound A and a chiral agent can be cited.

[0151] The second liquid crystal compound A may be a polymerizable liquid crystal compound having a polymerizable group.

[0152] As the second liquid crystal compound A, a polymerizable rod-like liquid crystal compound or a polymerizable discotic liquid crystal compound is preferred, and a polymerizable rod-like liquid crystal compound is more preferred from the viewpoint of reducing retardation in the thickness direction of the laminate.

[0153] As the polymerizable rod-like liquid crystal compound, for example, rod-like liquid crystal compounds described in claim 1 of JP-A-11-513019 or paragraphs 0026 to 0098 of JP-A-2005-289980 can be preferably used.

[0154] As the polymerizable discotic liquid crystal compound, for example, the discotic liquid crystal compounds described in paragraphs 0020 to 0067 of JP-A-2007-108732 or paragraphs 0013 to 0108 of JP-A-2010-244038 can be preferably used.

[0155] The second liquid crystal compound A may be used alone or in combination of two or more.

[0156] The content of the second liquid crystal compound A in the second composition A is not particularly limited, but is preferably 50% by mass or more, more preferably 70% by mass or more, based on the total solid content in the second composition A. The upper limit is not particularly limited, but is usually 90% by mass or less.

[0157] The solid content refers to a component that can form the second cholesteric liquid crystal layer A from which the solvent has been removed, and is considered a solid content even if the component is in a liquid state.

[0158] (Second surfactant A2)

[0159] The second composition A may contain a second surfactant A2. The second surfactant A2 is preferably a component that is easily concentrated on the air interface side of the coating film when the second composition A is applied and can control the alignment of the second liquid crystal compound A.

[0160] In the first embodiment, the second surfactant A2 is not particularly limited, and the second surfactant B2 used in the second embodiment described below is preferably used.

[0161] According to the above preferred embodiment, it is easy to adjust the dark line region width / dark line width ratio within the above range.

[0162] The content of the second surfactant A2 is preferably 0.01 to 1% by mass, and more preferably 0.05 to 0.5% by mass, based on the total solid content of the second composition A.

[0163] (Solvents and other ingredients)

[0164] The second composition A used in the first embodiment may contain a solvent and other components.

[0165] The solvent and other components that may be contained in the second composition A used in the first embodiment are the same as those in the first composition A of the first embodiment, and thus description thereof will be omitted.

[0166] <Base material>

[0167] The first embodiment of the laminate may include a substrate.

[0168] The substrate is preferably a transparent substrate. The term "transparent substrate" means a substrate having a transmittance of 60% or more in the visible light region, and the transmittance is preferably 80% or more, and more preferably 90% or more.

[0169] As a material constituting the substrate, for example, films of cellulose acylate, polycarbonate, polysulfone, polyethersulfone, polyacrylate, polymethacrylate, cyclic polyolefin, polyolefin, polyamide, polystyrene, and polyester can be used. Among them, cellulose acylate films, cyclic polyolefin, polyacrylate, or polymethacrylate are preferred. In addition, commercially available cellulose acetate films (for example, "TD80U" and "Z-TAC" manufactured by FUJIFI LM Corporation, etc.) can also be used.

[0170] Furthermore, from the viewpoint of suppressing the adverse effect on the polarization degree of transmitted light and facilitating optical inspection of the optical film, the support preferably has a small phase difference. Specifically, the size of Re is preferably 10 nm or less, and the absolute value of the size of Rth is preferably 50 nm or less.

[0171] The substrate may contain various additives (for example, an optical anisotropy adjuster, a wavelength dispersion adjuster, fine particles, a plasticizer, a UV blocker, a degradation inhibitor, a release agent, etc.).

[0172] The thickness of the substrate is not particularly limited, but is preferably 10 to 200 μm, more preferably 10 to 100 μm, and further preferably 20 to 90 μm.

[0173] Furthermore, the base material may be formed by laminating a plurality of sheets.

[0174] In order to improve the adhesion between the substrate and the layer provided thereon, the surface of the substrate may be subjected to a surface treatment (for example, glow discharge treatment, corona discharge treatment, ultraviolet (UV) treatment, and flame treatment).

[0175] As described above, the first embodiment of the laminated body of the present invention only needs to include the first cholesteric liquid crystal layer A and the second cholesteric liquid crystal layer A, and may include other structures.

[0176] Other structures include cholesteric liquid crystal layers other than the first and second cholesteric liquid crystal layers, adhesive layers, adhesion layers, alignment layers, antireflection layers, phase difference layers, and light absorption anisotropic layers.

[0177] In addition, the first embodiment of the laminate of the present invention may be a method in which the laminate has three or more cholesteric liquid crystal layers, and these layers are layers formed sequentially by coating using a composition containing a liquid crystal compound on each layer. Specifically, when the laminate sequentially has a cholesteric liquid crystal layer C1, a cholesteric liquid crystal layer C2, and a cholesteric liquid crystal layer C3, the method may be as follows: the cholesteric liquid crystal layer C2 is a layer formed by coating using a composition containing a liquid crystal compound on the cholesteric liquid crystal layer C1, and the cholesteric liquid crystal layer C3 is a layer formed by coating using a composition containing a liquid crystal compound on the cholesteric liquid crystal layer C2. In addition, in the case of the above method, the liquid crystal compound contained in at least one of the cholesteric liquid crystal layer C1 and the cholesteric liquid crystal layer C2 is a disc-shaped liquid crystal compound. For example, the liquid crystal compound contained in the cholesteric liquid crystal layer C1 may be a rod-shaped liquid crystal compound, the liquid crystal compound contained in the cholesteric liquid crystal layer C2 may be a disc-shaped liquid crystal compound, and the liquid crystal compound contained in the cholesteric liquid crystal layer C3 may be a rod-shaped liquid crystal compound. Furthermore, the liquid crystal compound contained in the cholesteric liquid crystal layer C1 may be a disc-shaped liquid crystal compound, the liquid crystal compound contained in the cholesteric liquid crystal layer C2 may be a rod-shaped liquid crystal compound, and the liquid crystal compound contained in the cholesteric liquid crystal layer C3 may be a disc-shaped liquid crystal compound.

[0178] In the above embodiment, the cholesteric liquid crystal layer C2 may correspond to the second cholesteric liquid crystal layer in relation to the cholesteric liquid crystal layer C1, and may correspond to the first cholesteric liquid crystal layer in relation to the cholesteric liquid crystal layer C3.

[0179] When the stacked body is composed of three or more cholesteric liquid crystal layers, the central wavelengths of the light reflected by the above layers may be the same or different. By stacking layers having different central wavelengths of light reflected by the above layers, for example, light in the entire visible light region can be reflected.

[0180] Furthermore, when the laminate is applied to a virtual reality display device, it is preferable to adjust the central wavelength of light reflected by each layer according to the wavelength of light emitted from the virtual reality display device.

[0181] The reflectance of the laminate is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more in the entire visible light region. The upper limit of the reflectance is 50% or less.

[0182] <Method for producing laminate>

[0183] The first embodiment of the laminate can be produced, for example, by the following method.

[0184] The method that can be cited includes coating the above-mentioned first composition A on the above-mentioned substrate, subjecting the coating film to orientation treatment and polymerization treatment to form the first cholesteric liquid crystal layer A, coating the above-mentioned second composition A on the first cholesteric liquid crystal layer A, subjecting the coating film to orientation treatment and polymerization treatment to form the second cholesteric liquid crystal layer A.

[0185] The alignment treatment is not particularly limited, and examples thereof include a method of applying an electric field to the coating film and a method of heating the coating film. Alternatively, an alignment film may be formed in advance before forming the coating film, and the coating film may be formed on the alignment film.

[0186] As a method for forming an alignment film, a method of rubbing a film formed of a known material can be cited, and a method of rubbing a coating film is preferred. The direction of the rubbing treatment is not particularly limited, and the best direction is appropriately selected according to the direction in which the liquid crystal compound is to be oriented. In addition, the substrate on which the coating film is formed can be rubbed to form the coating film on the rubbed substrate.

[0187] The rubbing treatment can be applied to a treatment method widely used as an alignment treatment process of an alignment film of an LCD (liquid crystal display), specifically, a method of rubbing the surface of an alignment film or a resin substrate in a certain direction using paper, gauze, felt, rubber, nylon fiber, polyester fiber, or the like.

[0188] The polymerization treatment is not particularly limited, but a method of irradiating ultraviolet rays is preferred. The irradiation of ultraviolet rays is also preferably carried out in an environment with a low oxygen concentration. In addition, in this specification, "ultraviolet rays" refers to electromagnetic waves mainly comprising electromagnetic waves with a wavelength of 200 to 400 nm, preferably mainly comprising electromagnetic waves with a wavelength of 300 to 400 nm. The light source of ultraviolet rays is not particularly limited, and a known light source can be used, and a filter or the like can be used to irradiate ultraviolet rays including any wavelength region. As the light source of ultraviolet rays, high-pressure mercury lamps, metal halide lamps, and light-emitting diodes (LEDs) can be cited.

[0189] The irradiation energy is preferably 5 mJ / cm 2 ~100J / cm 2 , more preferably 30 to 600 mJ / cm 2 , more preferably 100 to 400 mJ / cm 2 In order to promote the photopolymerization reaction, light irradiation may be performed under heating conditions.

[0190] After forming the second cholesteric liquid crystal layer A, in order to reduce the influence of the surfactant of other layers formed thereon, the surface of the second cholesteric liquid crystal layer A may be subjected to surface treatment (e.g., corona discharge treatment). For example, if the surface of the second cholesteric liquid crystal layer A is subjected to corona discharge treatment, the influence of the second surfactant A2 present near the surface of the second cholesteric liquid crystal layer A can be reduced. In the case where the surface of the second cholesteric liquid crystal layer A is subjected to corona discharge treatment, the second composition A used for forming the second cholesteric liquid crystal layer A preferably contains a rod-shaped liquid crystal compound as the second liquid crystal composition A.

[0191] In addition, after forming the first cholesteric liquid crystal layer A, it is preferred that the surface of the first cholesteric liquid crystal layer A is not subjected to surface treatment (e.g., corona discharge treatment). That is, after forming the first cholesteric liquid crystal layer A, it is preferred that the second composition A is applied without surface treatment. This is because, generally, if the above-mentioned treatment is performed, the orientation of the second cholesteric liquid crystal layer A may be reduced. More specifically, in the case where a liquid crystal layer containing a rod-shaped liquid crystal compound is generally formed on a liquid crystal layer containing a disc-shaped liquid crystal compound, if the surface of the liquid crystal layer containing the disc-shaped liquid crystal compound is subjected to corona treatment, the surface is hydrophilized. In a state where the surface of the liquid crystal layer containing the disc-shaped liquid crystal compound is hydrophilized, if a layer containing a rod-shaped liquid crystal compound is to be formed, the rod-shaped liquid crystal compound is generally hydrophobic, and therefore, the orientation of the rod-shaped liquid crystal compound may be reduced.

[0192] [Second Embodiment of Laminated Body]

[0193] The second embodiment of the laminate of the present invention is a laminate including a first cholesteric liquid crystal layer B and a second cholesteric liquid crystal layer B, wherein the first cholesteric liquid crystal layer B is formed using a first composition B containing a first liquid crystal compound B, and the second cholesteric liquid crystal layer B is formed on the first cholesteric liquid crystal layer B by coating using a second composition B containing a second liquid crystal compound B. Here, the first liquid crystal compound B contained in the first composition B is a discotic liquid crystal compound, and the first liquid crystal compound B and the second liquid crystal compound B are different compounds. Furthermore, the second cholesteric liquid crystal layer B contains a surfactant, and on the surface of the second cholesteric liquid crystal layer B on the side opposite to the first cholesteric liquid crystal layer B, the number of aggregates of the surfactant having a major diameter of 0.5 μm or more is less than 10,000 / mm 2 .

[0194] The cholesteric liquid crystal layer refers to a layer in which a cholesterically aligned liquid crystal compound is fixed.

[0195] The aggregate of the surfactant according to the second embodiment of the laminate will be described below.

[0196] The number of surfactant aggregates having a major axis of 0.5 μm or more on the surface of the second cholesteric liquid crystal layer B of the stacked body on the side opposite to the first cholesteric liquid crystal layer B side (hereinafter also referred to as “the surface of the second cholesteric liquid crystal layer B”) was determined as follows.

[0197] First, the surface of the second cholesteric liquid crystal layer B of the stack is analyzed by time-of-flight secondary ion mass spectrometry (TOF-SIMS) to obtain mapping data of the mass spectrum in the analysis area. In addition, TOF-SIMS is specifically described in "Surface Analysis Technology Series Secondary Ion Mass Spectrometry" compiled by the Japan Surface Science Society, Maruzen Co., Ltd. (published in 1999).

[0198] The detailed conditions of the analysis by TOF-SIMS can be measured, for example, under the conditions described in the Examples described later.

[0199] In the above analysis, the analysis area (e.g., 40 μm square) is set as a segment divided into 256 vertical and horizontal sections, for example, and an ion beam is irradiated to each segment of the analysis area to obtain a mass spectrum of secondary ions originating from the surface of the second cholesteric liquid crystal layer B. At this time, if the detection intensity of the secondary ions corresponding to the secondary ions originating from the surfactant contained in the second cholesteric liquid crystal layer B is mapped, the presence or absence of the agglomerates of the surfactant can be confirmed. In addition, the secondary ions originating from the surfactant refer to the fragment ions originating from the surfactant.

[0200] The secondary ions for mapping may be appropriately selected from the secondary ions derived from the surfactant according to the type of the surfactant and the components contained in the second cholesteric liquid crystal layer B, and are not limited to the ion types described below.

[0201] As secondary ions derived from surfactants, secondary ions (fragment ions) derived from groups contained in surfactants can be cited, and as groups contained in surfactants, for example, fluorinated alkyl groups, fluorinated alkoxy groups, fluorinated polyether groups, and organic groups having siloxane bonds (for example, groups having polysiloxane chains containing alkyl groups, groups having polysiloxane chains containing fluorinated alkyl groups, groups having polysiloxane chains containing acryloyl groups, etc.) can be cited. The fluorinated alkyl groups included in the groups listed above can be perfluoroalkyl groups in which all hydrogen atoms of the alkyl groups are substituted with fluorine atoms, or can be partially fluorinated alkyl groups in which part of the hydrogen atoms of the alkyl groups are substituted.

[0202] Next, in the image mapped with the detection intensity of the secondary ions corresponding to the secondary ions originating from the surfactant, the area where the portion with larger detection intensity is unevenly distributed and the agglomerate of the surfactant is confirmed is confirmed. For each area considered to be an agglomerate of the surfactant, the distance between the parallel lines when the distance between the two parallel lines in contact with the area becomes the longest is set as the major diameter of the agglomerate of the surfactant. Through the above steps, the number of agglomerates of the surfactant with a major diameter of 0.5 μm or more in the analysis area is counted.

[0203] The number of aggregates of the surfactant having a major axis of 0.5 μm or more in the analysis region was also counted for the other regions of the second cholesteric liquid crystal layer B, and the number of aggregates was counted for 10 locations. The arithmetic mean of the number of aggregates obtained from the 10 counts of the number of aggregates was divided by the area of ​​the analysis region to calculate the number of aggregates per unit area (unit: number / mm 2 ).

[0204] In the second embodiment of the laminate of the present invention, the number of aggregates per unit area obtained in this way is less than 10,000 pieces / mm 2 The number of aggregates per unit area is preferably 1000 / mm 2 Below, more preferably 100 pieces / mm 2 The lower limit of the number of aggregates per unit area is 0 / mm. 2 above.

[0205] In addition, when the surface of the second cholesteric liquid crystal layer B on the side opposite to the first cholesteric liquid crystal layer B is not exposed, if an ion beam is irradiated while cutting the outermost surface of the stack and an analysis based on TOF-SIMS is performed, the number of agglomerates on the surface of the second cholesteric liquid crystal layer B on the side opposite to the first cholesteric liquid crystal layer B can be obtained.

[0206] In addition, on the surface of the second cholesteric liquid crystal layer B on the side opposite to the first cholesteric liquid crystal layer B, the number of aggregates of the surfactant having a major axis of 0.5 μm or more is less than 10,000 / mm. 2 In the case of , the mechanism by which the reflectivity of the cholesteric liquid crystal layer increases is not necessarily clear, but it is presumed to be as follows. That is, it is believed that if the number of agglomerates of the surfactant is within the above range, the surfactant is likely to function effectively, and the orientation of the second liquid crystal compound B in the second cholesteric liquid crystal layer B is not easily disturbed. Therefore, it is believed that reflection in an undesirable direction due to the disordered orientation of the second liquid crystal compound B is suppressed, and the reflectivity of the cholesteric liquid crystal layer increases.

[0207] Hereinafter, each structure of the second embodiment of the laminate and the materials used in each structure will be described.

[0208] <First cholesteric liquid crystal layer B>

[0209] The second embodiment of the laminated body of the present invention includes a first cholesteric liquid crystal layer B formed using a first composition B containing a first liquid crystal compound B. That is, the first cholesteric liquid crystal layer B is a layer obtained by fixing the cholesterically aligned first liquid crystal compound B. Therefore, the first cholesteric liquid crystal layer B may contain components derived from components contained in the first composition B described later.

[0210] The layer formed by fixing the cholesterically oriented first liquid crystal compound B can be a layer in which the orientation morphology is not changed by an external field or external force. In addition, in the first cholesteric liquid crystal layer B, as long as the optical properties of the cholesteric liquid crystal phase are maintained in the layer, the first liquid crystal compound B in the first cholesteric liquid crystal layer B may no longer show liquid crystal properties. For example, the first liquid crystal compound B may be converted to a high molecular weight by a curing reaction, thereby losing its liquid crystal properties.

[0211] The first cholesteric liquid crystal layer B can reflect electromagnetic waves (light) in a specific wavelength range through the first liquid crystal compound B in a cholesteric orientation. The center wavelength λ of the light reflected by the first cholesteric liquid crystal layer B depends on the pitch P (= period of the spiral) of the spiral structure in the cholesteric liquid crystal phase, and is expressed by the relationship λ=n×P using the average refractive index n of the first cholesteric liquid crystal layer B. In addition, the center wavelength of the light reflected by the first cholesteric liquid crystal layer B can be obtained in the same manner as the center wavelength of the light reflected by the first cholesteric liquid crystal layer A of the first embodiment.

[0212] The central wavelength λ of the light reflected by the first cholesteric liquid crystal layer B is preferably in the visible light region.

[0213] The reflectance of the first cholesteric liquid crystal layer B at the central wavelength λ is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more. The upper limit of the reflectance is 50% or less.

[0214] The thickness of the first cholesteric liquid crystal layer B is preferably 0.1 to 10 μm, more preferably 0.3 to 5 μm.

[0215] <First Composition B>

[0216] The first composition B used for forming the first cholesteric liquid crystal layer B contains a first liquid crystal compound B. The first composition B preferably contains a first surfactant B1.

[0217] Hereinafter, the components contained in the first composition B and the components that may be contained will be described.

[0218] (First Liquid Crystalline Compound B)

[0219] The first liquid crystal compound B is not particularly limited as long as it is a discotic liquid crystal compound, and a known discotic liquid crystal compound can be used. The first liquid crystal compound B is selected to be a compound different from the second liquid crystal compound B described later. As a method for causing the first liquid crystal compound B to undergo cholesteric alignment, for example, a method using a first composition B comprising the first liquid crystal compound B and a chiral agent can be cited.

[0220] The first liquid crystal compound B may be a polymerizable liquid crystal compound having a polymerizable group. As the first liquid crystal compound B, a polymerizable discotic liquid crystal compound is more preferred.

[0221] Examples of compounds used as the first liquid crystal compound B are the same as those of the first liquid crystal compound A in the first embodiment, and thus description thereof is omitted.

[0222] (First surfactant B1)

[0223] The first composition B may contain a first surfactant B1. The first surfactant B1 is preferably a component that is easily concentrated on the air interface side of the coating film when the first composition B is applied and can control the alignment of the first liquid crystal compound B.

[0224] The first surfactant B1 preferably exhibits liquid crystal properties and has a phase transition temperature from a liquid crystal phase to an isotropic liquid phase of 100° C. or higher, or the first surfactant B1 is non-liquid crystal and has a melting point of 90° C. or higher. It is believed that when the above characteristics are satisfied, for example, when the first cholesteric liquid crystal layer B is formed on a substrate in a roll-to-roll manner, the first surfactant B1 is not easily transferred to the surface of the substrate on the side opposite to the first cholesteric liquid crystal layer B. If the first surfactant B1 is not easily transferred to the substrate, the coating film is likely to become uniform when the second cholesteric liquid crystal layer B is formed, and when the obtained laminate is used in a virtual reality display device, the image can be clearly visually recognized.

[0225] The first surfactant B1 is preferably not easily transferred to the substrate. The amount of transfer to the substrate can be estimated by the method described below. In addition, the method when the first surfactant B1 has a fluoroalkyl group is described below.

[0226] First, a first cholesteric liquid crystal layer is formed on a substrate. Next, the substrate with the first cholesteric liquid crystal layer is overlapped in such a manner that the surface of the first cholesteric liquid crystal layer formed on the side opposite to the substrate and the surface of the substrate on the side opposite to the first cholesteric liquid crystal layer are opposite to each other. In the overlapped state, a weight is placed on the substrate side at 45°C to apply a pressure of 0.01 MPa for 3 days. Then, the amount of fluorine on the surface of the substrate in contact with the surface of the first cholesteric liquid crystal layer on the side opposite to the substrate is analyzed by X-ray photoelectron spectroscopy.

[0227] The content of fluorine atoms as determined by X-ray photoelectron spectroscopy is preferably 10 atomic % or less, more preferably 5 atomic % or less, and further preferably 2 atomic % or less relative to all atoms. The lower limit of the content of fluorine atoms is 0 atomic % or more.

[0228] From the viewpoint of high solubility in the second composition B described later and the formed coating film, the first surfactant B1 is preferably a low molecular compound having no repeating unit, and the molecular weight of the first surfactant B1 as a low molecular compound is preferably 5000 or less. The molecular weight of the first surfactant B1 as a low molecular compound is more preferably 1000 to 5000, and further preferably 2000 to 4000.

[0229] Furthermore, from the viewpoint of the alignment control ability of the first liquid crystal compound B, the first surfactant B1 also preferably has three or more aromatic ring structures, and more preferably has four or more aromatic ring structures. Even when the aromatic ring structure is a condensed ring structure (e.g., a naphthalene ring), the number of aromatic ring structures is set to 1. Among them, when the aromatic ring structure is a condensed ring structure and the condensed ring structure is a phenanthrene ring, a fluorene ring, or an anthracene ring, the number of aromatic ring structures contained in the condensed ring structure is set to 2.

[0230] The first surfactant B1 preferably has a fluoroalkyl group, preferably a linear perfluoroalkyl group, from the viewpoint of being easily concentrated on the air interface side of the coating film and having high solubility in the second composition B described below and the formed coating film.

[0231] More specifically, the first surfactant B1 is preferably a compound represented by the following formula (11).

[0232] [Chemical formula 1]

[0233]

[0234] In the formula (11), Rf represents a linear perfluoroalkyl group.

[0235] When two or more Rf are included in formula (11), each Rf may represent the same group or different groups, but preferably represents the same group.

[0236] The linear perfluoroalkyl group preferably has 2 to 8 carbon atoms, more preferably 3 to 6 carbon atoms, and even more preferably 4 carbon atoms.

[0237] In formula (11), the number of Rf contained is preferably 2 to 9, more preferably 3 to 6, and even more preferably 3 or 4.

[0238] In formula (11), p1 represents an integer of 1 to 3. Among them, p1 is preferably 1-2.

[0239] In formula (11), A 11 Each independently represents a hydrocarbon group having a valence of p1+1. The hydrocarbon group having a valence of p1+1 may contain one or more atoms selected from the group consisting of oxygen atoms and nitrogen atoms.

[0240] By A 11 The p1+1-valent hydrocarbon group represented by is preferably 2 to 40 carbon atoms, more preferably 3 to 30 carbon atoms.

[0241] By A 11 The p1+1-valent hydrocarbon group represented by preferably includes an aliphatic hydrocarbon structure, an aromatic hydrocarbon structure, and a structure in which these structures are combined.

[0242] The aliphatic hydrocarbon structure may be linear or branched, or may include a cyclic structure. The aliphatic hydrocarbon structure preferably has 2 to 10 carbon atoms, more preferably 2 to 6 carbon atoms.

[0243] Examples of the aromatic hydrocarbon structure include a benzene structure and a naphthalene structure, among which a benzene structure is preferred.

[0244] By A 11 The p1+1-valent hydrocarbon group represented by may contain two or more atoms of one kind selected from the group consisting of oxygen atoms and nitrogen atoms.

[0245] In the formula (11), q1 represents an integer of 2 to 4.

[0246] Multiple p1 and A 11 They may be different or the same, but are preferably the same.

[0247] It is also preferred that q1 and p1 be set so that the number of Rf is within the above preferred range. For example, when p1 is 1, q1 is preferably 3, when p1 is 2, q1 is preferably 2 or 3, and when p1 is 3, q1 is preferably 2.

[0248] In formula (11), X 12It represents a q1+1-valent aromatic ring group.

[0249] By X 12 The q1+1-valent aromatic ring group represented by may be a monocyclic structure or a polycyclic structure.

[0250] By X 12 The q1+1-valent aromatic ring group represented by may contain heteroatoms other than carbon atoms (for example, one or more atoms selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom).

[0251] As X 12 Examples of the q1+1-valent aromatic ring group represented by include a group obtained by removing q1+1 hydrogen atoms from a compound selected from the group consisting of benzene and naphthalene.

[0252] In formula (11), X 13 Each independently represents a divalent aromatic ring group which may have a substituent.

[0253] By X 13 The aromatic ring group represented may be a monocyclic structure or a polycyclic structure.

[0254] By X 13 The aromatic ring group represented by may contain hetero atoms other than carbon atoms (for example, one or more atoms selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom).

[0255] As X 13 The aromatic ring group represented by X may be a group formed by removing two hydrogen atoms from a compound selected from the group consisting of benzene, naphthalene, anthracene, phenanthrene and 1,2,4-oxadiazole. In addition, the position where the hydrogen atom is removed is not particularly limited. For example, 13 When the aromatic ring group represented by is a group obtained by removing two hydrogen atoms from benzene, the position of the other hydrogen atom with respect to one hydrogen atom may be any position, but is preferably the para position.

[0256] And, in the 13 When the aromatic ring group represented is a group formed by removing two hydrogen atoms from naphthalene, the position of the other hydrogen atom relative to one hydrogen atom can be any one of ortho (1, 2 positions), meta (1, 3 positions), para (1, 4 positions), sub (1, 5 positions), epi (1, 6 positions), hypo (1, 7 positions), peri (1, 8 positions), meta (2, 3 positions) and sub (2, 6 positions), preferably para, sub or meta.

[0257] As X 13 The substituents that the aromatic ring group represented by may have include -CN, -R3, -OR3, -OH, -(CH2) mOne or more substituents selected from the group consisting of -OH, -F, -COOR3 and -COR3. R3 represents a linear or branched alkyl group having 1 to 20 carbon atoms. m represents an integer of 1 to 3. The number of carbon atoms of the alkyl group represented by R3 is preferably 1 to 6, more preferably 1 to 4. Examples of the alkyl group represented by R3 include methyl, ethyl, 1-propyl, 2-propyl, 1-butyl and tert-butyl.

[0258] By X 13 The substituent that the aromatic ring group represented by is may have is preferably one or more substituents selected from the group consisting of -R3, -OR3, -COOR3 and -COR3.

[0259] In formula (11), L 13 and L 14 Each independently represents a single bond, -CO-, -COO-, -CONR1-, -O-, -(CH2) n -、-(CH2) n -O-, -O-(CH2) n -、-CO-CH=CH-、-COO-(CH2) n - or -C≡C-. R1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an integer of 1 to 3.

[0260] L 13 Preferably it is a single bond, -COO-, -CONR1-, -O- or -COO-(CH2) n -, more preferably a single bond, -COO- or -CONR1-, further preferably a single bond or -COO-, and particularly preferably -COO-.

[0261] L 14 Preferred are single bonds, -CO-, -COO-, -CONR1-, -O-, -(CH2) n -、-O-(CH2) n -、-COO-(CH2) n -, -CO-CH=CH- or -C≡C-, more preferably a single bond, -COO- or -CONR1-, further preferably a single bond or -COO-, and particularly preferably -COO-.

[0262] In formula (11), r1 represents an integer from 0 to 4. 14 In the case of -COO-CH2-, r1 represents 0.

[0263] When r1 is 2 or more, L 13 and X 13 The groups represented may be different from each other or the same.

[0264] r1 is preferably 1-3, and more preferably 1 or 2.

[0265] Furthermore, in formula (11), it is also preferred that r1 is 2 or more, or r1 is 1, and X 13 It is a divalent aromatic ring group having multiple ring structures.

[0266] In formula (11), X 14 Indicates that it can be -CN, -R2, -OR2, -OH, -(CH2) m A monovalent aromatic ring group substituted with -OH, -F or -CO OR2, or a group having the following structure.

[0267] [Chemical formula 2]

[0268]

[0269] In the above structure, * indicates 14 bonding position.

[0270] R2 represents a linear or branched alkyl group having 1 to 20 carbon atoms. m represents an integer of 1 to 3.

[0271] The carbon number of the alkyl group represented by R2 is preferably 1 to 12, more preferably 1 to 8. Examples of the alkyl group represented by R2 include methyl, ethyl, propyl, butyl, propyl, hexyl, heptyl, and octyl. R2 is preferably a linear alkyl group.

[0272] The substituent that may substitute the aromatic ring group is also preferably selected according to the liquid crystal compound used in the liquid crystal composition described later.

[0273] By X 14 The aromatic ring group represented may be a monocyclic structure or a polycyclic structure.

[0274] By X 14 The aromatic ring group represented by may contain hetero atoms other than carbon atoms (for example, one or more atoms selected from the group consisting of a nitrogen atom, an oxygen atom, and a sulfur atom).

[0275] Examples of the monocyclic structure include phenyl and pyridyl, and examples of the polycyclic structure include naphthyl, anthracenyl, phenanthrenyl, fluorenyl, benzofuranyl, benzimidazolyl, and benzothiazolyl.

[0276] X 14 It is also preferred that the aromatic ring group represented has no substituent as described above.

[0277] The first surfactant B1 represented by the above formula (11) is preferably a compound represented by the following formula (12).

[0278] [Chemical formula 3]

[0279]

[0280] In the formula (12), Rf represents a linear perfluoroalkyl group.

[0281] When two or more Rf are included in formula (12), each Rf may represent the same group or different groups, but preferably represents the same group.

[0282] The linear perfluoroalkyl group preferably has 2 to 8 carbon atoms, more preferably 3 to 6 carbon atoms, and even more preferably 4 carbon atoms.

[0283] In formula (12), the number of Rf is preferably 2 to 9, more preferably 3 to 6, and even more preferably 3 or 4.

[0284] In formula (12), p2 represents an integer of 1 to 3.

[0285] In formula (12), X 21 It represents a single bond, a p2+1-valent aromatic ring group, or a p2+1-valent aliphatic hydrocarbon group having 3 to 10 carbon atoms.

[0286] By X 21 The p2+1-valent aromatic ring group represented by may be a monocyclic structure or a polycyclic structure.

[0287] As X 21 The p2+1-valent aromatic ring group represented by : may be a group formed by removing p2+1 hydrogen atoms from a compound selected from the group consisting of benzene and naphthalene. Among them, a group formed by removing p2+1 hydrogen atoms from benzene is preferred.

[0288] By X 21 The aliphatic hydrocarbon group having 3 to 10 carbon atoms and having a valence of p2+1 represented by may be linear or branched, and may also include a cyclic structure.

[0289] As X 21 The p2+1-valent aliphatic hydrocarbon group having 3 to 10 carbon atoms represented by the above-mentioned group includes, for example, a group formed by removing p2+1 hydrogen atoms from a compound selected from the group consisting of n-propane, n-butane, n-pentane, n-hexane, isobutane, 3-ethylpentane, neopentane, neohexane, cyclobutane and cyclohexane. Among them, a group formed by removing p2+1 hydrogen atoms from n-propane is preferred.

[0290] In addition, in X 21 When it represents a single bond, p2 is 1.

[0291] In formula (12), L 21 It represents a divalent linking group represented by the following formulae (2-1) to (2-4).

[0292] [Chemical formula 4]

[0293]

[0294] In formulas (2-1) to (2-4), p represents an integer of 1 to 3.

[0295] In formulas (2-1) to (2-4), ** represents 21 , and * represents the bonding position with Rf.

[0296] In formula (12), q2 represents an integer of 2 to 4.

[0297] Multiple p2, L 21 , X 21 and L 22 They may be different or the same, and are preferably the same.

[0298] q2 and p2 are also preferably set so that the number of Rf is within the above preferred range. For example, when p2 is 1, q2 is preferably 3, when p2 is 2, q2 is preferably 2 or 3, and when p2 is 3, q2 is preferably 1 or 2.

[0299] In formula (12), X 22 It represents a q2+1-valent aromatic ring group.

[0300] By X 22 The q2+1-valent aromatic ring group represented by may be a monocyclic structure or a polycyclic structure.

[0301] As X 22 The q2+1-valent aromatic ring group represented by X 12 The same is true for the q1+1-valent aromatic ring group represented by .

[0302] In formula (12), X 23 Each independently represents a divalent aromatic ring group which may have a substituent.

[0303] By X 23 The aromatic ring group represented may be a monocyclic structure or a polycyclic structure.

[0304] As X 23 The aromatic ring group represented by X 13 The preferred aspects are also the same for the aromatic ring groups represented.

[0305] And, X 23 Substituents that can be present are the same as X 13 The substituents that may be possessed are the same, and the preferred aspects are also the same.

[0306] In formula (12), L 22 , L 23 and L 24 Each independently represents a single bond, -CO-, -COO-, -CONR1-, -O-, -(CH2) n -、-(CH2) n -O-, -O-(CH2) n -、-CO-CH=CH-、-COO-(CH2) n - or -C≡C-. R1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an integer of 1 to 3.

[0307] L 22 Preferably it is a single bond, -COO-, -CONR1-, -O- or -COO-(CH2) n -, more preferably a single bond, -O- or -COO-.

[0308] L 23 Preferably it is a single bond, -COO-, -CONR1-, -O- or -COO-(CH2) n -, more preferably a single bond, -COO- or -CONR1-, further preferably a single bond or -COO-, and particularly preferably -COO-.

[0309] L 24 Preferred are single bonds, -CO-, -COO-, -CONR1-, -O-, -(CH2) n -、-O-(CH2) n -、-COO-(CH2) n -, -CO-CH=CH- or -C≡C-, more preferably a single bond, -COO- or -CONR1-, further preferably a single bond or -COO-, and particularly preferably -COO-.

[0310] In formula (12), r2 represents an integer of 0 to 4. 24 In the case of -CO-O-CH2-, r2 represents 0.

[0311] r2 is preferably 1-3.

[0312] In formula (12), X 24 Indicates that it can be -CN, -R2, -OR2, -OH, -(CH2) m -OH, -F or -OC OOR2 substituted monovalent aromatic ring group. R2 represents a linear or branched alkyl group having 1 to 20 carbon atoms. m represents an integer of 1 to 3. Specific examples and preferred embodiments of R2 are the same as those of R2 described in formula (11).

[0313] By X 24 The aromatic ring group represented may be a monocyclic structure or a polycyclic structure.

[0314] X 24 The aromatic ring group represented by may contain heteroatoms other than carbon atoms (for example, one or more atoms selected from the group consisting of nitrogen atoms, oxygen atoms, and sulfur atoms). 24 Specific examples and preferred embodiments of the aromatic ring group represented by are the same as those of X in formula (11): 14 The specific examples and preferred embodiments are the same.

[0315] The first surfactant B1 represented by the above formula (11) is a low molecular weight compound having no repeating unit, and therefore is considered to have high solubility in the second composition B described later and the coating film formed. In addition, it is considered that since the molecule includes a group similar to a rigid unit (for example, a group including an aromatic ring group called a mesogen group) contained in the structure of a liquid crystal, the alignment control capability of the first liquid crystal compound B is high.

[0316] If the first surfactant B1 represented by the above formula is used, when the second cholesteric liquid crystal layer B is formed on the formed first cholesteric liquid crystal layer B by coating treatment, the first surfactant B1 has high solubility with respect to the second composition B, thereby being able to uniformly coat the second composition B, thereby easily and uniformly forming the second cholesteric liquid crystal layer B. In addition, it is considered that the first surfactant B1 dissolved in the second composition B is concentrated on the air interface side of the coating film of the second composition B, but since the solubility in the coating film formed by the second composition B is high, it is not easy to form an aggregate derived from the first surfactant B1. As a result, if the first surfactant B1 is used when forming the first cholesteric liquid crystal layer B, it is easy to adjust the number of aggregates of the above-mentioned surfactant of the second cholesteric liquid crystal layer B within the above-mentioned range.

[0317] (Solvents and other ingredients)

[0318] The first composition B used in the second embodiment may contain a solvent and other components.

[0319] The solvent and other components that may be contained in the first composition B used in the second embodiment are the same as those in the first composition A of the first embodiment, and thus description thereof will be omitted.

[0320] <Second cholesteric liquid crystal layer B>

[0321] The second embodiment of the laminated body of the present invention includes a second cholesteric liquid crystal layer B, which is formed on the first cholesteric liquid crystal layer B by coating using a second composition containing a second liquid crystal compound B. That is, the second cholesteric liquid crystal layer B is a layer obtained by fixing the cholesterically aligned second liquid crystal compound B. Therefore, the second cholesteric liquid crystal layer B may include components derived from the components included in the second composition B described later.

[0322] The layer formed by fixing the cholesterically oriented second liquid crystal compound B can be a layer in which the orientation morphology is not changed by an external field or external force. In addition, in the second cholesteric liquid crystal layer B, as long as the optical properties of the cholesteric liquid crystal phase are maintained in the layer, the second liquid crystal compound B in the second cholesteric liquid crystal layer B may no longer exhibit liquid crystal properties. For example, the second liquid crystal compound B may be converted to a high molecular weight by a curing reaction, thereby losing liquid crystal properties.

[0323] The second cholesteric liquid crystal layer B can reflect electromagnetic waves (light) in a specific wavelength range through the cholesterically oriented second liquid crystal compound B. The center wavelength λ of the light reflected by the second cholesteric liquid crystal layer B depends on the pitch P (= period of the spiral) of the spiral structure in the cholesteric liquid crystal phase, and is expressed by the relationship λ=n×P using the average refractive index n of the second cholesteric liquid crystal layer B. In addition, the center wavelength of the light reflected by the second cholesteric liquid crystal layer B can be obtained in the same manner as the center wavelength of the light reflected by the first cholesteric liquid crystal layer A.

[0324] The central wavelength λ of the light reflected by the second cholesteric liquid crystal layer B is preferably in the visible light region.

[0325] The reflectance of the second cholesteric liquid crystal layer B at the central wavelength λ is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more. The upper limit of the reflectance is 50% or less.

[0326] Furthermore, the second cholesteric liquid crystal layer B contains a surfactant.

[0327] As described above, in the laminate of the second embodiment, the number of aggregates of the surfactant having a major axis of 0.5 μm or more on the surface of the second cholesteric liquid crystal layer B opposite to the first cholesteric liquid crystal layer B is less than 25 / mm. 2 , preferably 10 / mm 2 The lower limit of the number of surfactant aggregates having a major diameter of 0.5 μm or more is 0 / mm. 2 .

[0328] The surfactant contained in the second cholesteric liquid crystal layer B preferably includes a first surfactant and a second surfactant of different types.

[0329] The first surfactant is preferably the first surfactant B1 contained in the first composition B for forming the first cholesteric liquid crystal layer B. Furthermore, the second surfactant is preferably the second surfactant B2 contained in the second composition B for forming the second cholesteric liquid crystal layer B described later.

[0330] The thickness of the second cholesteric liquid crystal layer B is preferably 0.1 to 10 μm, more preferably 0.3 to 5 μm.

[0331] <Second Composition B>

[0332] The second composition B used for forming the second cholesteric liquid crystal layer B contains a second liquid crystal compound B.

[0333] Hereinafter, the components contained in the second composition B and the components that may be contained will be described.

[0334] (Second Liquid Crystalline Compound B)

[0335] The second liquid crystal compound B is not particularly limited, and a known liquid crystal compound can be used. The second liquid crystal compound B is selected to be a compound different from the first liquid crystal compound B. Examples of the liquid crystal compound include rod-shaped liquid crystal compounds and disc-shaped liquid crystal compounds. As a method for making the second liquid crystal compound B cholesterically oriented, for example, a method using a first composition B containing a second liquid crystal compound B and a chiral agent can be mentioned.

[0336] The second liquid crystal compound B may be a polymerizable liquid crystal compound having a polymerizable group.

[0337] The second liquid crystal compound B is preferably a discotic liquid crystal compound, and more preferably a polymerizable discotic liquid crystal compound.

[0338] Examples of the compound used as the second liquid crystal compound B are the same as those of the second liquid crystal compound A in the first embodiment, and thus description thereof is omitted.

[0339] (Second surfactant B2)

[0340] The second composition B may contain a second surfactant B2. The second surfactant B2 is preferably a component that is easily concentrated on the air interface side of the coating film when the second composition B is applied and can control the alignment of the second liquid crystal compound B.

[0341] Examples of the second surfactant B2 include conventionally known surfactants, and fluorine-based compounds are preferred.

[0342] As a fluorine-based compound, a polymer fluorine-based compound containing a repeating unit having a fluorine-containing group is preferably included. As the fluorine-containing group of the above-mentioned repeating unit having a fluorine-containing group, a fluorine-containing alkyl group is preferably included. The fluorine-containing alkyl group can be a perfluoroalkyl group or a partially fluorinated alkyl group. The polymer fluorine-based compound can include other repeating units except the repeating unit having a fluorine-containing group. As other repeating units, repeating units having a group containing a ring structure can be cited. As a group containing a ring structure, a group containing an aromatic ring structure and a group containing an alicyclic structure can be cited. Heteroatoms other than carbon atoms (e.g., oxygen atoms, nitrogen atoms) can be included in the above-mentioned ring structure.

[0343] Examples of the fluorine-based compound include compounds described in paragraphs 0028 to 0056 of JP-A-2001-330725 and compounds described in paragraphs 0069 to 0126 of JP-A-2005-062673.

[0344] In addition, the second surfactant B2 may be the compound described in the first surfactant B1.

[0345] (Solvents and other ingredients)

[0346] The second composition B used in the second embodiment may contain a solvent and other components.

[0347] The solvent and other components that may be contained in the second composition B used in the second embodiment are the same as those in the first composition A of the first embodiment, and thus description thereof will be omitted.

[0348] <Base material>

[0349] The second embodiment of the laminate may include a substrate.

[0350] Preferred aspects of the substrate that may be included in the second embodiment of the laminate are the same as preferred aspects of the substrate that may be included in the first embodiment, and thus description thereof will be omitted.

[0351] The second embodiment of the laminated body of the present invention only needs to include the first cholesteric liquid crystal layer B and the second cholesteric liquid crystal layer B as described above, but may include other structures.

[0352] Other structures include cholesteric liquid crystal layers other than the first cholesteric liquid crystal layer B and the second cholesteric liquid crystal layer B, adhesive layers, adhesion layers, alignment layers, antireflection layers, phase difference layers, and light absorption anisotropic layers.

[0353] Furthermore, when the laminate is applied to a virtual reality display device, it is preferable to adjust the central wavelength of light reflected by each layer according to the wavelength of light emitted from the virtual reality display device.

[0354] The reflectance of the laminate is preferably 40% or more, more preferably 45% or more, further preferably 47% or more, and particularly preferably 49% or more in the entire visible light region. The upper limit of the reflectance is 50% or less.

[0355] <Method for producing laminate>

[0356] The second embodiment of the laminate can be produced by, for example, the following method.

[0357] The method that can be cited includes coating the above-mentioned first composition B on the above-mentioned substrate, orienting and polymerizing the coated film to form the first cholesteric liquid crystal layer B, coating the above-mentioned second composition B on the first cholesteric liquid crystal layer B, orienting and polymerizing the coated film to form the second cholesteric liquid crystal layer B.

[0358] As the above-mentioned alignment treatment, for example, a heating treatment can be mentioned. And as the polymerization treatment, for example, an irradiation treatment with activating light can be mentioned. In addition, when the first composition B or the second composition B contains a solvent, a treatment for removing the solvent contained in the coating film can be performed.

[0359] In order to include a surfactant in the second cholesteric liquid crystal layer B, the first cholesteric liquid crystal layer B may be formed using the second composition B including a surfactant or using the first composition B including a surfactant having high solubility in the second composition B.

[0360] Furthermore, the surface treatment, orientation treatment, and polymerization treatment are the same as those in the method for producing the laminate described in the first embodiment.

[0361] In addition, after forming the first cholesteric liquid crystal layer B, it is preferred that the surface of the first cholesteric liquid crystal layer B is not subjected to surface treatment (e.g., corona discharge treatment). That is, it is preferred that after forming the first cholesteric liquid crystal layer B, the second composition B is applied without surface treatment. This is because, generally, if the above-mentioned treatment is performed, the orientation of the second cholesteric liquid crystal layer B may be reduced. More specifically, in the case where a liquid crystal layer containing a rod-shaped liquid crystal compound is usually formed on a liquid crystal layer containing a disc-shaped liquid crystal compound, if the surface of the liquid crystal layer containing the disc-shaped liquid crystal compound is subjected to corona treatment, the surface is hydrophilized. In a state where the surface of the liquid crystal layer containing the disc-shaped liquid crystal compound is hydrophilized, if a layer containing a rod-shaped liquid crystal compound is to be formed, the rod-shaped liquid crystal compound is generally hydrophobic, and therefore, the orientation of the rod-shaped liquid crystal compound may be reduced.

[0362] [Virtual reality display device]

[0363] The virtual reality display device of the present invention includes the laminated body of the present invention.

[0364] In the virtual reality display device of the present invention, the laminate of the present invention is preferably used as a reflective polarizer. In particular, the laminate of the present invention is preferably used as a reflective polarizer in a virtual reality display device having a reciprocating optical system that reflects and reciprocates light between a reflective polarizer and a half mirror.

[0365] The structure of the reflective optical system and the structure of the virtual reality display device can be referred to Japanese Patent Application Publication No. 7-120679 and Japanese Patent Application Publication No. 2017-227720, etc.

[0366] Example

[0367] Hereinafter, the present invention will be described in further detail based on examples.

[0368] The materials, usage amounts, ratios, treatment contents and treatment procedures shown in the following examples can be appropriately changed without departing from the gist of the present invention. Therefore, the scope of the present invention should not be interpreted in a limiting sense by the following examples.

[0369] [Manufacturing of Laminated Body]

[0370] The laminate used in the examples and comparative examples was manufactured according to the following steps. Specifically, first, a composition containing a liquid crystal compound was applied to a substrate, and a predetermined treatment was performed to form a cholesteric liquid crystal layer. A composition containing a liquid crystal compound was applied to the formed cholesteric liquid crystal layer, and a predetermined treatment was performed to form a cholesteric liquid crystal layer, thereby obtaining a laminate.

[0371] Hereinafter, each composition and a method for forming a cholesteric liquid crystal layer will be described.

[0372] <Composition>

[0373] The compositions shown below are all compositions for forming a cholesteric liquid crystal layer. In addition, a composition marked with a symbol including "R" means a composition including a rod-like liquid crystal compound, and a composition marked with a symbol including "D" means a composition including a discotic liquid crystal compound.

[0374] (Composition R-1)

[0375] The following components were stirred and dissolved in a container kept at 70° C. to prepare composition R-1.

[0376]

[0377] Rod-like liquid crystal compound A1 (mixing ratio is mass ratio)

[0378] [Chemical formula 5]

[0379]

[0380] Rod-like liquid crystal compound A2

[0381] [Chemical formula 6]

[0382]

[0383] Photopolymerization initiator B

[0384] [Chemical formula 7]

[0385]

[0386] Chiral reagent A1

[0387] [Chemical formula 8]

[0388]

[0389] In addition, the chiral reagent A1 is a chiral reagent (chiral reagent A) whose helical twisting power (HTP: Helical Twisting Power) is reduced by light.

[0390] Surfactant F1 (ratio of repeating units is mass ratio)

[0391] [Chemical formula 9]

[0392]

[0393] (Composition R-2)

[0394] Composition R-2 was prepared in the same manner as in Composition R-1, except that the amount of chiral agent A1 added was changed to 3.63 parts by mass and the amount of surfactant F1 added was changed to 0.15 parts by mass.

[0395] (Composition D-1)

[0396] The components shown below were stirred and dissolved in a container kept at 50° C., thereby preparing composition D-1.

[0397]

[0398]

[0399] Discotic liquid crystal compound (A)

[0400] [Chemical formula 10]

[0401]

[0402] Discotic liquid crystal compound (B)

[0403] [Chemical formula 11]

[0404]

[0405] Polymerizable monomer E1

[0406] [Chemical formula 12]

[0407]

[0408] Surfactant F2

[0409] [Chemical formula 13]

[0410]

[0411] In addition, the surfactant F2 is non-liquid crystal and has a melting point of 94° C. Furthermore, the number of aromatic ring structures contained in the surfactant F2 is four.

[0412] Pyridinium Salt A

[0413] [Chemical formula 14]

[0414]

[0415] Boric acid monomer A

[0416] [Chemical formula 15]

[0417]

[0418] (Composition D-2)

[0419] Composition D-2 was prepared in the same manner as in Composition D-1 except that the amount of chiral reagent A1 added was changed to 5.28 parts by mass.

[0420] (Composition D-3)

[0421] Composition D-3 was prepared in the same manner as in composition D-1, except that surfactant F2 was changed to the following surfactant F3.

[0422] Surfactant F3

[0423] [Chemical formula 16]

[0424]

[0425] In addition, the surfactant F3 is non-liquid crystal and has a melting point of 50° C. Furthermore, the number of aromatic ring structures contained in the surfactant F3 is 3.

[0426] (Composition D-4)

[0427] Composition D-3 was prepared in the same manner as in composition D-2, except that surfactant F2 was changed to the above-mentioned surfactant F3.

[0428] (Composition D-5)

[0429] Composition D-5 was prepared in the same manner as in composition D-1, except that surfactant F2 was changed to the following surfactant F4.

[0430] Surfactant F4

[0431] [Chemical formula 17]

[0432]

[0433] In addition, surfactant F4 is non-liquid crystal and has a melting point of 108°C.

[0434] (Composition D-6)

[0435] Composition D-6 was prepared in the same manner as in composition D-2, except that surfactant F2 was changed to the above-mentioned surfactant F4.

[0436] (Composition D-7)

[0437] The composition was prepared in the same manner as in Composition D-1 except that the amount of the chiral reagent A1 added was changed to 3.1 parts by mass.

[0438] (Composition D-8)

[0439] Preparation was carried out in the same manner as D-1 except that the discotic liquid crystal compound (C) was used instead of the discotic liquid crystal compounds (A) and (B).

[0440] Discotic Liquid Crystalline Compounds (C)

[0441] [Chemical formula 18]

[0442]

[0443] (Composition D-9)

[0444] The composition was prepared in the same manner as in Composition D-1 except that the amount of the chiral reagent A1 added was changed to 4.1 parts by mass.

[0445] (Composition D-10)

[0446] The composition D-8 was prepared in the same manner as in the composition D-8 except that the amount of the chiral reagent A1 added was changed to 4.6 parts by mass.

[0447] <Steps for producing laminate>

[0448] The laminated bodies used in Examples and Comparative Examples were obtained by the following procedures.

[0449] (Laminate 1)

[0450] As a pseudo support, a PET (polyethylene terephthalate) film (A4100 manufactured by TOYOBO CO., LTD.) having a thickness of 50 μm was prepared. The PET film had an easy-adhesion layer on one side.

[0451] The surface of the PET film without the easy-adhesion layer was subjected to rubbing treatment, and the composition R-1 was applied by a wire bar coater to form a coating film, which was then dried at 110° C. for 120 seconds. The coating film was then maintained at 80° C. and irradiated with ultraviolet light (illuminance 100 mW / cm2) from a metal halide lamp in a nitrogen atmosphere (oxygen concentration 100 ppm or less). 2 , irradiation dose 250mJ / cm 2 ) was used to fix the orientation direction of the liquid crystal compound, and a cholesteric liquid crystal layer 1 was formed on the PET film. The ultraviolet light was irradiated from the coating film side. In addition, the coating amount of the composition R-1 was adjusted so that the film thickness of the formed cholesteric liquid crystal layer 1 became 4.5 μm.

[0452] The cholesteric liquid crystal layer 1 is a cholesteric liquid crystal layer that reflects red light (central wavelength of reflected light: 650 nm). The cholesteric liquid crystal layer 1 does not belong to either the first cholesteric liquid crystal layer or the second cholesteric liquid crystal layer of the present invention.

[0453] Next, the surface of the cholesteric liquid crystal layer 1 opposite to the PET film side was discharged at a discharge rate of 150 W·min / m 2 After the corona treatment, the composition D-1 was applied to the corona treated surface by a wire bar coater to form a coating film. Next, the coating film was dried at 70°C for 2 minutes and then heated at 103°C for 3 minutes to obtain a uniform orientation state. The coating film was then maintained at 45°C and irradiated with ultraviolet light (illuminance 100 mW / cm2) from a metal halide lamp in a nitrogen atmosphere (oxygen concentration 100 ppm or less). 2 , irradiation dose 250mJ / cm 2) to fix the orientation direction of the liquid crystal compound, and a cholesteric liquid crystal layer 2 was formed on the cholesteric liquid crystal layer 1. The ultraviolet light was irradiated from the coating film side. In addition, the coating amount of the composition D-1 was adjusted so that the film thickness of the formed cholesteric liquid crystal layer 2 became 3.3 μm.

[0454] The cholesteric liquid crystal layer 2 is a cholesteric liquid crystal layer that reflects yellow light (central wavelength of reflected light: 600 nm). The cholesteric liquid crystal layer 2 corresponds to the first cholesteric liquid crystal layer of the present invention.

[0455] Next, the composition R-2 was applied to the surface of the cholesteric liquid crystal layer 2 on the side opposite to the PET film side using a wire bar coater to form a coating film, and then the coating film was dried at 110° C. for 120 seconds. Then, the coating film was maintained at 80° C. and irradiated with ultraviolet light (illuminance 100 mW / cm2) from a metal halide lamp in a nitrogen atmosphere (oxygen concentration 100 ppm or less). 2 , irradiation dose 250mJ / cm 2 ) to fix the orientation direction of the liquid crystal compound, and a cholesteric liquid crystal layer 3 was formed on the cholesteric liquid crystal layer 2. The ultraviolet light was irradiated from the coating film side. In addition, the coating amount of the composition R-2 was adjusted so that the film thickness of the formed cholesteric liquid crystal layer 3 became 2.7 μm.

[0456] The cholesteric liquid crystal layer 3 is a cholesteric liquid crystal layer that reflects green light (central wavelength of reflected light: 550 nm). The cholesteric liquid crystal layer 3 corresponds to the second cholesteric liquid crystal layer of the present invention.

[0457] Next, the surface of the cholesteric liquid crystal layer 3 opposite to the PET film side was discharged at a discharge amount of 150 W·min / m 2 After the corona treatment, the composition D-2 was applied to the corona treated surface by a wire bar coater to form a coating film. Next, the coating film was dried at 70°C for 2 minutes and then heated at 100°C for 3 minutes to obtain a uniform orientation state. Then, the coating film was maintained at 45°C and irradiated with ultraviolet light (illuminance 100 mW / cm2) from a metal halide lamp in a nitrogen atmosphere (oxygen concentration 100 ppm or less). 2 , irradiation dose 250mJ / cm 2 ) to fix the orientation direction of the liquid crystal compound, and a cholesteric liquid crystal layer 4 was formed on the cholesteric liquid crystal layer 3. The ultraviolet light was irradiated from the coating film side. In addition, the coating amount of the composition D-2 was adjusted so that the film thickness of the formed cholesteric liquid crystal layer 4 became 2.5 μm.

[0458] The cholesteric liquid crystal layer 4 is a cholesteric liquid crystal layer that reflects blue light (central wavelength of reflected light: 460 nm). The cholesteric liquid crystal layer 4 does not belong to either the first cholesteric liquid crystal layer or the second cholesteric liquid crystal layer of the present invention.

[0459] The laminated body 1 is obtained through the above steps.

[0460] (Laminate 2)

[0461] Laminated body 2 was obtained by the same procedure as that of laminated body 1 except that composition D-3 was used instead of composition D-1 and composition D-4 was used instead of composition D-2.

[0462] (Laminate 3)

[0463] Laminate 3 was obtained by the same steps as laminate 1, except that composition D-7 was used instead of composition R-1, composition D-8 was used instead of composition D-1, composition D-9 was used instead of composition R-2, and composition D-10 was used instead of composition D-2.

[0464] In addition, when laminating each layer, the conditions for applying the composition D-1 to form the cholesteric liquid crystal layer 2 were applied. That is, corona treatment was performed before applying each composition.

[0465] (Laminate 4)

[0466] Laminated body 4 was obtained by the same procedure as that of laminated body 1 except that composition D-5 was used instead of composition D-1 and composition D-6 was used instead of composition D-2.

[0467] [Measurement]

[0468] <Measurement of agglutination>

[0469] In the above steps, for the sample in the state of the cholesteric liquid crystal layer 3 prepared in the stacked bodies 1 to 3, the surface of the cholesteric liquid crystal layer 3 on the opposite side to the cholesteric liquid crystal layer 2 was analyzed by TOF-SIMS, the secondary ions derived from the surfactant were mapped, and the number of agglomerates derived from the surfactant was counted.

[0470] <Measurement of dark line area width / dark line width ratio>

[0471] According to the above-mentioned steps, the dark line region width / dark line width ratio of the laminates 1 to 4 were obtained.

[0472] The observation was performed using "S-4800" manufactured by Hitachi High-Tech Corporation. In the observation using SEM, the acceleration voltage was set to 2 kV, and a secondary electron image was acquired at a magnification of 20,000 times.

[0473] In any of the laminated bodies, the value of the ratio of the region width Wrb to the width Wb (region width Wrb / width Wb) was 1.0.

[0474] <Transfer of surfactant>

[0475] The degree of transfer of the surfactant from the cholesteric liquid crystal layer 2 to the substrate was evaluated by X-ray photoelectron spectroscopy using the above method.

[0476] In the table at the latter stage, the following criteria are used for description.

[0477] A: The content of fluorine atoms is less than 2 atomic % relative to all atoms

[0478] B: The content of fluorine atoms is 2 atomic % or more and less than 5 atomic % relative to all atoms

[0479] C: The content of fluorine atoms is 5 atomic % or more relative to all atoms

[0480] [evaluate]

[0481] <Reflectivity>

[0482] The reflectance of the laminated bodies 1 to 4 was measured using a spectrophotometer (V-550 manufactured by JASCO Corporation). In addition, the reflectance of each of the cholesteric liquid crystal layers 1 to 4 was measured at the center wavelength of the reflected light.

[0483] <Evaluation of image clarity>

[0484] In Example 1, the lens of the virtual reality display device "Huawei VR Glass" manufactured by Huawei Technologies Co., Ltd., which uses a reciprocating optical system, was disassembled, and the lens closest to the visual recognition side was removed. The visual recognition side of the lens is a convex plano-convex lens, and a reflective circular polarizer is bonded to the plane side. The reflective circular polarizer is peeled off from the lens, and the optical laminate sheet 1 of the manufacturing method shown in the later section is bonded to the plane side in such a way that the absorption polarizer side becomes the visual recognition side. The lens bonded with the optical laminate sheet 1 is assembled again on the main body to produce a virtual reality display device.

[0485] Similarly, virtual reality display devices used in Examples 2 and 3 and Comparative Example 1 were produced.

[0486] In the virtual reality display devices of Examples 1 to 3 and Comparative Example 1, a black and white grid pattern was displayed on the image display device, and the degree of image clarity was visually evaluated according to the following criteria. If the image clarity is poor, part or all of the grid pattern will be distorted.

[0487] A: The distortion of the grid pattern is barely noticeable.

[0488] B: The distortion of the grid pattern is slightly noticeable, but it is not a big deal

[0489] C: The distortion of the grid pattern is clearly visible

[0490] (Fabrication of optical laminated sheets)

[0491] Optical laminate sheets 1 to 4 were produced using the laminates 1 to 4 described above.

[0492] The following is a typical production procedure of an optical layer sheet 1 using layered product 1. Optical layer sheets 2 to 4 using layered products 2 to 4 were also produced in the same procedure as described below.

[0493] First, an ultraviolet curing adhesive "ARONIX UVX-6282" manufactured by TOAGOSEI CO., LTD. was applied to an antireflection film "AR200-T0810-JD" manufactured by Dexerials Corporation. Next, the laminate 1 and the antireflection film were laminated so that the cholesteric liquid crystal layer 4 of the laminate 1 and the applied adhesive layer faced each other. In the laminated state, ultraviolet rays (300 mJ / cm 2 ) to cure the adhesive. After curing the adhesive, the PET film of the laminate 1 is peeled off and removed to obtain a laminate sheet. The laminate sheet has an anti-reflection film, an adhesive layer, a cholesteric liquid crystal layer 4, a cholesteric liquid crystal layer 3, a cholesteric liquid crystal layer 2 and a cholesteric liquid crystal layer 1 in this order.

[0494] The thickness of the adhesive layer after curing was 35 μm, and the refractive index of the adhesive layer after curing was 1.48.

[0495] The λ / 4 phase difference plate was bonded and adhered to the surface of the stacked sheet on the cholesteric liquid crystal layer 1 side using the above-mentioned adhesive, and the absorption type polarizer was further bonded and adhered to the surface of the λ / 4 phase difference plate on the side opposite to the cholesteric liquid crystal layer 1 side using the above-mentioned adhesive. When bonding the absorption type polarizer, the direction was adjusted so that the angle formed by the slow axis of the λ / 4 phase difference plate and the absorption axis of the absorption type polarizer was 45°.

[0496] The thickness of the adhesive layer after curing was 35 μm.

[0497] Next, an adhesive sheet "NCF-D692 (15)" manufactured by LINTEC Corporation was attached to the absorption polarizer to obtain an optical laminate sheet 1. The optical laminate sheet 1 sequentially comprises an antireflection film, an adhesive layer, a cholesteric liquid crystal layer 4, a cholesteric liquid crystal layer 3, a cholesteric liquid crystal layer 2, a cholesteric liquid crystal layer 1, an adhesive layer, a λ / 4 phase difference plate, an adhesive layer, an absorption polarizer, and an adhesive sheet. In addition, in the obtained optical laminate sheet 1, the number of foreign matters with a side length of 30 μm or more was 1:1 per 1 m. 2 There are 90 in total.

[0498] The obtained optical laminated sheet 1 was cut into a circle with a diameter of 35 mm using a picosecond laser processing machine. In addition, a portion of the end was cut off to form a notch in a manner indicating the orientation of the absorption axis of the absorption-type polarizer. In addition, during processing, the processing conditions were adjusted so that the angle of the cut end face relative to the vertical direction of the optical laminated sheet 1 was less than 5°.

[0499] <Evaluation of Double Vision>

[0500] In the virtual reality display devices of Examples 1 to 3 and Comparative Example 1 produced in the evaluation of image clarity, the image display device was made to display a black and white grid pattern, and the degree of ghosting was visually evaluated according to the following criteria. In addition, if ghosting occurs, the ghosting can be visually recognized, and the contrast of the part where the ghosting can be visually recognized is reduced.

[0501] A: Almost no double image can be seen

[0502] B: Slightly visible double images, but no problem

[0503] C: Ghosting is clearly visible

[0504] [result]

[0505] Table 1 shows the structure of the laminate and the measurement results and evaluation results of the laminate.

[0506] [Table 1]

[0507]

[0508] The results in Table 1 show that the cholesteric liquid crystal layer has high reflectance in the laminated body of the example. On the other hand, in the laminated body of the comparative example where the dark line region width / dark line width ratio is not within the prescribed range or the number of aggregates is greater than the prescribed value, the reflectance of the second cholesteric liquid crystal layer is low.

[0509] By comparing Example 1 with Example 2, it was confirmed that when the surfactant (first surfactant) used in the cholesteric liquid crystal layer 2 is non-liquid crystal and has a melting point of 90° C. or higher, the reflectivity of the cholesteric liquid crystal layer is better and the image clarity is better. In addition, it was confirmed that the transfer of the surfactant (first surfactant) is also less.

[0510] Comparison between Example 1 and Example 2 shows that when the surfactant (first surfactant) used in the cholesteric liquid crystal layer 2 has an aromatic ring structure with four or more rings, the reflectivity of the cholesteric liquid crystal layer is better and the image clarity is better.

[0511] Comparison between Example 1 and Example 2 shows that when the surfactant (first surfactant) used in the cholesteric liquid crystal layer 2 is the surfactant represented by the above formula (11), the reflectivity of the cholesteric liquid crystal layer is better and the image clarity is better.

[0512] By comparing Examples 1 and 2 with Example 3, it was confirmed that ghosting is less likely to occur when the cholesteric liquid crystal layers 1 and 3 contain rod-like liquid crystal compounds and the cholesteric liquid crystal layers 2 and 4 contain disc-like liquid crystal compounds (the first liquid crystal compound is a disc-like liquid crystal compound and the second liquid crystal compound is a rod-like liquid crystal compound).

[0513] Explanation of symbols

[0514] 100 - laminated body, 10 - first cholesteric liquid crystal layer, 12 - second cholesteric liquid crystal layer, 26 - second liquid crystal layer bright line, 28 - second liquid crystal layer dark line, 28a - surface dark line, 28b - middle dark line, M - middle position.

Claims

1. A laminate comprising: a first cholesteric liquid crystal layer formed using a first composition including a first liquid crystal compound; and a second cholesteric liquid crystal layer formed on the first cholesteric liquid crystal layer by coating with a second composition containing a second liquid crystal compound; The first liquid crystal compound is a discotic liquid crystal compound, The first liquid crystal compound and the second liquid crystal compound are different compounds, and When, among the bright lines and dark lines derived from the cholesteric liquid crystal phase of the second cholesteric liquid crystal layer observed by cross-section observation using a scanning electron microscope, the dark line at the position farthest from the first cholesteric liquid crystal layer side is defined as a surface dark line, and the dark line at the position closest to the middle position in the thickness direction of the second cholesteric liquid crystal layer is defined as a middle dark line, A ratio of a width of a region where the surface dark line exists in a thickness direction of the second cholesteric liquid crystal layer to a width of the intermediate dark line in the thickness direction of the second cholesteric liquid crystal layer is 1.2 or less.

2. The laminate according to claim 1, wherein A ratio of a width of a region where the middle dark line exists in a thickness direction of the second cholesteric liquid crystal layer to a width of the middle dark line in the thickness direction of the second cholesteric liquid crystal layer is 3.0 or less.

3. A laminate comprising: a first cholesteric liquid crystal layer formed using a first composition including a first liquid crystal compound; and a second cholesteric liquid crystal layer formed on the first cholesteric liquid crystal layer by coating with a second composition containing a second liquid crystal compound; The first liquid crystal compound is a discotic liquid crystal compound, The first liquid crystal compound is different from the second liquid crystal compound, The second cholesteric liquid crystal layer includes a surfactant, On the surface of the second cholesteric liquid crystal layer on the side opposite to the first cholesteric liquid crystal layer, the number of aggregates of the surfactant having a major diameter of 0.5 μm or more is less than 10,000 / mm 2 .

4. The laminate according to claim 3, wherein: The surfactant includes a first surfactant and a second surfactant.

5. The laminate according to claim 4, wherein The first surfactant is a surfactant contained in the first composition, The first surfactant is liquid crystal, and the phase transition temperature from the liquid crystal phase to the isotropic liquid phase is 100° C. or more, or The first surfactant is non-liquid crystal and has a melting point of 90° C. or higher.

6. The laminate according to claim 5, wherein The first surfactant has an aromatic ring structure having four or more rings.

7. The laminate according to claim 5, wherein The molecular weight of the first surfactant is 5,000 or less.

8. The laminate according to claim 5, wherein The first surfactant is represented by the following formula (11): In formula (11), Rf represents a linear perfluoroalkyl group, In formula (11), p1 represents an integer from 1 to 3, In formula (11), A 11 Each independently represents a hydrocarbon group having a valence of p1+1, wherein the hydrocarbon group may contain one or more atoms selected from the group consisting of oxygen atoms and nitrogen atoms, In formula (11), q1 represents an integer of 2 to 4, In formula (11), X 12 represents a q1+1 valent aromatic ring group, In formula (11), X 13 Each independently represents a divalent aromatic ring group which may have a substituent, In formula (11), L 13 and L 14 Each independently represents a single bond, -CO-, -COO-, -CONR1-, -O-, -(CH2) n -、-(CH2) n -O-, -O-(CH2) n -、-CO-CH=CH-、-COO-(CH2) n - or -C≡C-, R1 represents a hydrogen atom or an alkyl group having 1 to 3 carbon atoms, and n represents an integer of 1 to 3, In formula (11), r1 represents an integer from 0 to 4, wherein 14 In the case of -COO-CH2-, r1 represents 0, In formula (11), X 14 Indicates that it can be -CN, -R2, -OR2, -OH, -(CH2) m -OH, -F or -CO OR2 substituted monovalent aromatic ring group, or a group representing the following structure, in which * represents the same structure as L 14 The bonding position of R2 represents a linear or branched alkyl group having 1 to 20 carbon atoms, and m represents an integer of 1 to 3.

9. The laminate according to claim 3, wherein: The second liquid crystal compound is a rod-shaped liquid crystal compound.

10. A virtual reality display device comprising the laminated body according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Manufacture of aminoarylsulfonic acid

    JP1988280056A

  • Homocentric optical system

    JP1995120679A

  • polymerizable liquid crystal compound

    JP1999513019A

  • Optical compensation sheet, elliptically polarizing plate and liquid crystal display device

    JP2001330725A

  • Optically anisotropic layer, method for manufacturing the same, retardation plate using the same, elliptically polarizing plate and liquid crystal display

    JP2005062673A